The Effect of Providing Creative Dance Education on Early Childhood Self-Confidence at TK/Mother's Daycare Center - Kartika Tri Amalia; Ramita Ramita; Shofiyatul Af-Idah; Mayang Sari Sitorus; Hilda Zahra Lubis (Pusdikra-Publishing.com, 2024)
This qualitative study investigates how teaching creative dance impacts children's self-confidence at Ibunda Kindergarten. The phenomenological method was used in this study to understand children's perceptions and experiences during the creative dance program. Participatory observation, in-depth interviews and document analysis were the methods used to collect data. The study involved 15 early childhood children from Ibunda Kindergarten. The results showed that teaching children creative dance increased their own self-confidence. Creation dance teaches social skills, working together in a group, and self-expression. They also showed increased initiative and independence. The findings confirm that arts education is an important component of the early childhood education curriculum as it can help with psychosocial development.